THE EFFECT OF AUDIT STANDARDS, ETHICS, INDEPENDENCE, COMPETENCE, AND AUDITOR'S EXPERIENCE ON AUDITOR'S PROFESSIONALISM SKEPTICISM IN KAP IN MEDAN CITY - salim, Feronica Susanna; Tjitra, Jocelyn; Malau, Yois Nelsari; Ginting, Wenny Anggresia (Journal Accounting International Mount Hope, 2025)
This study aims to analyze the influence of audit standards, ethics, independence, competence, and auditor experience on auditor professional skepticism in Public Accounting Firms (KAP) in Medan City. The approach used in this study is a quantitative approach, which is carried out on a certain population or sample in order to test the established hypothesis. The study population includes all auditors working at KAP Medan City, although the exact number is unknown or biased. Because the population is not known with certainty, the sampling technique used is the Lemeshow formula. This approach allows the calculation of the number of samples in uncertain population conditions, so that 96 respondents are obtained. The sampling technique applied is accidental sampling, where respondents are selected randomly to be part of the research sample. The results of the study indicate that audit standards, ethics, independence, competence, and auditor experience have a positive and significant effect on auditor professional skepticism, both partially and simultaneously.